Cities for life : how communities can recover from trauma and rebuild for health - Corburn, Jason (Island Press, 2021)
"Imagine a city that actively works to promote the health and healing of all of its residents. What if that city acknowledges its part in creating the traumas that cause unhealthy stress, such as segregated neighborhoods, insecure housing, few playgrounds, environmental pollution, and unsafe streets, particularly for the poor and Black, Indigenous, People of Color (BIPOC)? In Cities for Life, public health expert Jason Corburn shares lessons from three of these cities: Richmond, California; Medellín, Colombia; and Nairobi, Kenya. Corburn draws from his work with citizens, activists, and decision-makers in these cities over a ten-year period, as individuals and communities worked to heal from trauma-from gun violence, housing and food insecurity, and poverty. These communities found innovative solutions for urban trauma by respecting the lived experience of those who were most impacted by harms. Cities for Life is essential reading for urban planning, design, and public health professionals as they work to change an urban planning and public health model that for too long has blamed the urban poor and BIPOC for how they have responded to traumas that they didn't create"-- $c Provided by publisher.